Orientaciones pedagógicas que enriquezcan las prácticas evaluativas universitarias desde TIC y Ludoevaluación (Memorias Sifored - Encuentros Educación UAN, 2022)
In this writing, pedagogical guidelines are proposed related to the design, development and evaluation of experiences enriched with Ludoevaluación, an alternative strategy to traditional assessment, which takes advantage of the benefits provided by Information and Communication Technologies (ICT) and the principles pedagogical aspects of Ludoevaluation. This idea arises due to the fact that in higher education it is evident that the development of evaluative practices focused on qualifying and categorizing students still persists, which is why it is necessary to resignify the entrenched technical strategies and return the gaze to the formative and rewarding sense of formative assessment. That is why the transformation potential that ICT can generate compared to evaluative methodologies is recognized. The research is methodologically framed from a qualitative approach and uses several of the stages that structure the ADDIE and ASSURE instructional design models. At the end of this study, the results are the construction of pedagogical orientations to be considered from the theoretical, pedagogical, methodological and technical fields for ludoevaluative experiences with the potential to be implemented as support for university assessment processes.
Keywords: Assessment; Ludoevaluación; ICT; Higher Education; innovation